2018
DOI: 10.1177/0309132518768407
|View full text |Cite
|
Sign up to set email alerts
|

Environmental values, knowledge and behaviour: Contributions of an emergent literature on the role of ethnicity and migration

Abstract: Amidst calls for paradigm shifts in environmental scholarship, we track an emergent literature on how environmental values, knowledge and behaviour (EVKB) change (or not) with the migration process. We focus on the role of Majority World migrants to the Minority World. Large-scale survey research into EVKB is beginning to consider both ethnicity and migration history as important variables, but tends to leave the concepts of environment and environmental behaviour unexamined. Western EVKB indicators thus tend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 82 publications
(127 reference statements)
0
15
0
Order By: Relevance
“…They found that there was a gap between White and African American students on their concerns for the environment. However, many of the cross-ethnic environmental studies conducted in the following decades have produced highly conflicting evidence with regard to the conceptualization of pro-environmental behaviors in different ethnic groups (for a review, see Head et al, 2018). In this article, we first review past studies on environmental belief and behavior selectively from both national surveys and regional representative samples (excluding convenience samples), paying attention to the emergence of ethnicity.…”
mentioning
confidence: 99%
“…They found that there was a gap between White and African American students on their concerns for the environment. However, many of the cross-ethnic environmental studies conducted in the following decades have produced highly conflicting evidence with regard to the conceptualization of pro-environmental behaviors in different ethnic groups (for a review, see Head et al, 2018). In this article, we first review past studies on environmental belief and behavior selectively from both national surveys and regional representative samples (excluding convenience samples), paying attention to the emergence of ethnicity.…”
mentioning
confidence: 99%
“…And yet the views and ideas of local people, or “nonexperts,” may entail “contradictory or conflicting needs, desires and interest” to that of science (Felli & Castree, 2012, p. 2). Narratives that marginalize “nonexpert” knowledge are gradually being challenged, opening up questions “of whose and what sorts of environmental knowledge count/s, and in what circumstances” (Head et al, 2019, p. 398). Local knowledge is increasingly understood as providing alternative understandings and insights.…”
Section: Ways Of Knowingmentioning
confidence: 99%
“…Importantly, local knowledge is not restricted to Indigenous people or the insights of people in the so‐called Global South; it might include, for example, the worldviews and insights of people living in the UK, US, Australia, and elsewhere (cf., Graham et al, 2014; Reineman et al, 2017; Thomas et al, 2015). Local knowledge is recognized as critical for detecting, understanding, responding, and adapting to environmental and climatic change (Ford et al, 2016; Head et al, 2019; Shawoo & Thornton, 2019).…”
Section: Ways Of Knowingmentioning
confidence: 99%
“…There is much to be learnt from engaging cross-cultural forms of learning (Head et al 2018;MacGregor et al 2019;Walker 2020) and engaging with Indigenous knowledge's (Schlosberg & Carruthers 2010) in relation to climate change. However, there has been a tendency to position climate action and activism as white and originating in the Global North (Jones 2020).…”
Section: Notementioning
confidence: 99%